Trialing a novel intubation equipment: A bidirectional tube with a flexible video stylet. (August 2020) - Ho, Geoffrey; Chu, Everett; Lee, Kyung Min; Rahimi, Murwarit; Hindle, Anna K.; Pla, Raymond; Benjenk, Ivy; Heinz, Eric
Abstract: Background: Video-laryngoscopy has proven valuable in management and training of difficult airways. We evaluate the Yann tube, a novel bi-directional articulable endotracheal tube and video stylet combination, together with video-laryngoscopy in a simulation setting to determine if it improves management and education of difficult airways. Methods: We evaluated the Yann tube (with video-laryngoscopy) against direct and video-laryngoscopy alone across four simulated airway scenarios, and measured time and attempts to successful intubation, percentage-of-glottic-opening (POGO) score, and Cormack-Lehane grading. Afterward, we surveyed participant subjective experiences. Results: There were 32 participants of varying experience. Pharyngeal obstruction was the only airway scenario where the Yann tube was significantly slower than video-laryngoscopy alone (37s vs 27s; p < 0.01), in exchange for improved glottic views, regarding POGO (75.2% vs 56.4%; p < 0.05) and Cormack-Lehane (1.4 vs 1.9; p < 0.01) scores. Students reported significantly greater confidence with intubation and airway anatomy understanding after simulation (p < 0.001). Conclusions: Although the Yann tube did not significantly improve successful first pass intubation, it did not significantly take longer to perform, and improved airway visualization in certain difficult airway scenarios. The use of simulation also enhanced education and understanding of airway anatomy for novice intubators. Highlights: A bi-directional articulable endotracheal tube with a customized video stylet improved visualization of the airway. Equipment that allow dynamic visualization are valuable training tools for airway management. Simulation is a valuable tool for trialing novel airway equipment.